A Study of Student Science Process Skills: In Formal Change Practices - Rinjani, Rinjani; Romadona, Dinda Desma (Schrödinger: Journal of Physics Education, 2023)
Research Objectives: This study aims to describe students' science process skills in the transformation practicum using an m-module based manual. Methodology: This study used a descriptive qualitative approach involving 40 physics education students at Jambi University. The sampling technique used is total sampling. The data collection instrument used the observation sheet of science process skills. The science process skills that are focused are basic science process skills, namely communication and measuring as well as integrated science process skills making graphs and describing relationships between variables. Main Findings: The results of this research were Jambi university physics education students who had good science process skills, especially measurement skills, 65% of the 40 students were in the very good category. This is also influenced by the effective use of e-modules and m-modules that are attractive to students. Novelty/Originality of Research: The effectiveness of the use of the m-module is seen in the good basic abilities of students in the practice of changing forms. Therefore, basic science process skills influence the development of integrated science process skills, where communication and measurement skills are part of basic science process skills.